Implementation of a Hazard Reporting System for Work Risk Mitigation at MT. Al Daayen - Maulana, Muhammad Daffa; Lestari, Elise Dwi; Dahri, Muh.; Sutoyo (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Work safety is a critical priority in maritime operations, particularly within the high-risk environment of tanker vessels. In accordance with International Maritime Organization (IMO) regulations, hazard reporting constitutes a fundamental pillar of the Safety Management System (SMS), designed to mitigate risks and foster a proactive safety culture. This study investigates the effectiveness of Hazard Report implementation on the MT. Al Daayen, specifically analyzing its impact on accident prevention behaviors and identifying the obstacles impeding consistent crew participation. Adopting a qualitative descriptive approach, this research utilizes Miles and Huberman’s interactive model to analyze data gathered through structured interviews, direct field observations, and longitudinal documentation reviews. The results demonstrate that the system has significantly enhanced safety culture, evidenced by heightened crew vigilance, consistent PPE adherence, and a measurable decline in near-miss incidents between 2021 and 2024. However, the study reveals that implementation remains suboptimal due to low participation from ratings. The analysis isolates critical barriers: human factors, including a lack of confidence and psychological fears of assigning blame; methodological constraints caused by lengthy, impractical forms; and environmental pressures, where the fast-paced operational tempo compels crew members to prioritize immediate rectification over formal documentation. The study concludes that simplifying reporting mechanisms is essential for ensuring inclusive safety engagement.